Critical success factors for the implementation of Instant Messaging in South African organisations - van Niekerk Kuys, Anfried (My University, 2011)
Instant messaging (IM) is a software application that allows instant text communication between two or more people through a network such as the Internet. IM is a faster and simpler way to communicate than e-mail, as it allows users to talk to one another in real time. It is becoming increasingly popular and the issue facing corporations is how they can leverage the use of instant messaging to make business more efficient without opening the organisation to the potential risks and disadvantages associated with IM. Effective integration of IM into business can have tremendous business potential if leveraged correctly. The purpose of this research is to establish the critical success factors that organisations in South African should consider before, during and after the implementation of Instant Messaging as an internal business communications medium. This research makes five propositions as to which factors highlighted by the literature are critical to the successful implementation of IM in South African organisations. Through the use of a survey as the research instrument, response data from 50 respondents were collected over a three month period to test the validity of these propositions. After analysis of the collected data, the five propositions were slightly amended. Two factors, IM client application and ease of use and Organisation’s technology use, were found to be the most critical factors when considering the implementation of IM in South African organisations. It is very important for organisations to realise the risk of not doing anything in terms of IM. If IM is not officially sanctioned or else prohibited, employees can download consumer-grade IM themselves and start using it. Once it is installed and active, it is very difficult to turn off as consumer IM services can breach nearly any corporate firewall through various deceptive methods. The challenge to organisations is to make IM part of the business process rather than a maverick technology
MBA - WBS
Keywords: Instant messaging; Mobile communications; Cell phones